Educação, ética, interculturalidade e saberes decoloniais - Carvalho, Alonso Bezerra de (Editora Oficina Universitária, 2023)
In addition to a discussion that seems to be in fashion, the purpose of this book is to contribute, in fact, to the reflections and practices that streamline and move the school environment. When one intends to articulate ethics, training, interculturality and decoloniality to think about education, he wants to dialogue not only with the researchers of the themes dealt with here, but above all to reach the school and classroom environment. It is in these places that, effectively, emerge challenging situations that, more often than not, people have difficulties in understanding, recognizing and building solutions. Always resorting to more of the same, what usually happens is a superficial and shallow look at the concerns and dramas that generate these challenges, problems and conflicts. That type of teacher training, which predominates in teacher training courses, seems to ask for a new meaning and meaning, as it is no longer able to respond and meet the demands and expectations of school training. Perhaps it is necessary to go beyond an education guided only by reason or by an idea or ideal of being human, but to take the reflections of classic and contemporary authors in order to enable us to include the ethical and aesthetic dimension in order to contribute to the construction of a process pedagogical approach that has freedom and human autonomy as its starting point and telos. The classroom is more than a place where knowledge is merely transmitted, but a space for coexistence, joy, exchange of affection and knowledge. We know that the people who are there carry passions, drives, feelings and a history that needs to be valued and taken into account.